110k views
4 votes
select all that applyA. Vertically stretch by a factor of 3.B. Vertically compress by a factor of 3.c. Shift right 1 unit.D. Shift down 1 unit.

select all that applyA. Vertically stretch by a factor of 3.B. Vertically compress-example-1
User I A Khan
by
5.6k points

1 Answer

2 votes

A vertical stretch/compression is given by the transformation below


\begin{gathered} h(x)\rightarrow a*h(x) \\ a>1\rightarrow\text{ stretch by a factor of a} \\ 0And a vertical shift is given by the following transformation[tex]\begin{gathered} h(x)\rightarrow h(x)+b \\ b>0\rightarrow\text{ b units up} \\ b<0\rightarrow\text{ b units down} \end{gathered}

Therefore, in our case,


\begin{gathered} f(x)=x\rightarrow(1)/(3)x\Rightarrow\text{ vertical compression by a factor of 3} \\ (1)/(3)x\rightarrow(1)/(3)x-1=g(x)\rightarrow\text{ vertical shift 1 unit down} \end{gathered}

Thus, the answer is options B and D

User Ifrah
by
6.5k points